Sacred aid faith and humanitarianism - Barnett, Michael N., 1960-; Stein, Janice Gross (New York ; Oxford : Oxford University Press, 2012)
Collectively, the chapters in this volume comprise an original and authoritative account of how religion has reshaped the global humanitarian movement in recent times.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Humanitarian assistance; Church work with disaster victims